A brief assessment of researchers' perceptions towards research data in India. (March 2017) - Tripathi, Manorama; Chand, Mahesh; Sonkar, S. K.; Jeevan, V. K. J.
The present paper dwells upon the importance of raw data for the development of science and research. The study includes an interview of 40 researchers and faculty members to understand their perception towards the raw data. It has suggested that the libraries can play a pivotal role in extending support to the researchers for organizing, archiving and preserving raw data for future use. Libraries may evolve a system at the university level wherein the researchers and faculty members be encouraged to deposit their raw research data in the institutional repositories, which most of the university libraries have developed.